The Relationship between Oil Price Volatility and Macroeconomic Variables in Nigeria: A Vector Autoregressive (VAR) Approach - Okoli, Tochukwu Timothy; Tewari, Devi Datt; Rhodaoluwafisayomi, Ajibola (Journal of Economics and Behavioral Studies, 2018)
Nigeria as an oil exporting mono-economy is susceptible to fluctuations in the world oil prices. About 97 percent of the government’s revenues are gotten from proceeds from oil export. The study attempts to assess the behaviors of macroeconomic variables in the face of oil price volatility in Nigeria. The empirical evidences reveal that macroeconomic variables were susceptibility to volatility in Oil Price. The theoretical framework is based on the Mundel-Flaming model and adopts the variance decomposition and impulse response functions to explain the dynamic properties of the VAR methodology. The impulse response results reveal that a one standard deviation in oil price will trigger a significant change in RGDP, GEXP, INFLATION and IMPORT both in the short and long run, and IR and EXR significantly only in the short run. Finally, the variance decomposition of RGDP, GEXP and EXR reveals that the variability in them were significantly explained by oil price volatility and other tests ran reveals a consistent result. Therefore, volatility in oil price has direct impact on real GDP, Government expenditure, inflation, interest rate, exchange rate and import. The researchers therefore recommend diversification of the economy to other sectors, financial prudence, sound fiscal policy and the lowering of interest rate to stimulate domestic investment.